Efficacy of lactose-free formula in acute diarrheal management for children under 5 years: a systematic review and meta-analysis - Putri, Ayu Maghfira Nida; Witarto, Andro Pramana; Yofi, Fadhil Abiyyu; Suasti, Ni Made Adnya; Alawiyah, Kania (Indonesian Pediatric Society, 2024)
Background Acute diarrhea is the most common gastrointestinal disease in children under five years of age with high morbidity and mortality risk. The use of lactose-free formula in the management of children with acute diarrhea was said to accelerate the diarrheal resolution time. Objective To determine the efficacy of lactose-free formula in managing acute diarrhea in pediatric patients by systematic review and meta-analysis. Methods A comprehensive literature search was conducted on PubMed, Proquest, Web of Science, and CINAHL Plus Database from November 1971 to July 11th, 2021. The study selection process was carried out under PRISMA 2020 guidelines based on several eligibility criteria. The quality of the included studies were further assessed using Modified Jadad Scores. Results Fifteen randomized controlled trials (RCTs) were included, involving a total of 1,390 children with acute diarrhea. Shorter recovery time (MD -0.21; 95%CI -0.50 to 0.08; P=0.16) was observed in patients receiving lactose-free formula than the control group. However, this finding was not statistically significant. The subgroup analysis showed that lactose-free formula significantly shortened the recovery time compared to oral rehydration solution (ORS) group (MD -0.70; 95%CI -0.98 to -0.41; P=0.00001). Furthermore, lactose-free formula also significantly reduced the amount of stool output (MD -0.61; 95%CI -0.86 to -0.36; P=0.00001) and the incidence of persistent diarrhea more than seven days (OR 0.22; 95%CI 0.10 to 0.51; P=0.0004) compared to the control group. Conclusion Lactose-free formula as dietary management for acute diarrhea in children can reduce stool output and the incidence of persistent diarrhea for more than seven days. It also may shorten the recovery time compared to the administration of ORS alone.